Short-term use of an exposed polypropylene barrier in the preservation of alveolar bone after extraction: randomized clinical trial. Issue 9 (September 2021) - dos Santos, C.C.V.; Tonini, K.R.; Silva, M.A.A.; de Carvalho, P.S.P.; Ponzoni, D.
Abstract: This study was performed to evaluate the short-term preservation of alveolar bone volume with or without a polypropylene barrier and exposure of the area after extractions. Thirty posterior tooth extraction sockets were distributed randomly to a control group ( n  = 15; extraction and suture) and a barrier group ( n  = 15; extraction, barrier, and suture). All sutures and barriers were removed 10 days postoperatively. Cone beam computed tomography scans taken with the aid of a tomographic guide were obtained preoperatively, immediately postoperative, and at 120 days postoperative. A visual analysis of the coronal sections of the alveolus was performed, and vertical loss in the mesial, distal, buccal, and lingual bone ridges and horizontal thickness were evaluated. The mean vertical loss after extraction did not differ significantly between the control and barrier groups (Student t -test: mesial P  =  0.989, buccal P  =  0.997, lingual/palatal P  =  0.070, distal P  =  0.107). The mean vertical loss at 120 days postoperative did not differ significantly between the control (0.65 mm) and barrier (0.52 mm) groups ( P  >  0.05), with an effect size of 0.13 mm. At 120 days, the barrier group presented a mean resorption in thickness (0.45 mm) that was significantly lower than that in the control group (0.76 mm) ( P  =  0.021), with an effect size of 0.31 mm. The polypropylene barrier reduced the horizontal resorption in sockets of posterior teeth after extraction.